A NEEDS ANALYSIS OF ESP FOR FASHION DESIGN STUDENTS AT AN INDONESIAN VOCATIONAL SCHOOL - Munir, Arfiana; Darwis, Nirwana; Hidayat, LD. Dian; Nur, Hasriati (International Journal of Research on English Teaching and Applied Linguistics, 2025)
This research analyzes the ESP learning needs of fashion design students at SMKN 1 Bone, focusing on how English learning can be aligned with the practical and professional demands of the fashion field. This study aims to identify how students perceive their English language needs, their current competencies and difficulties, as well as their preferences for English topics, materials, and learning methods relevant to the fashion field. Using a qualitative descriptive method, data were collected through questionnaires administered to 32 students and interviews with 8 purposively selected participants. The needs analysis framework follows Hutchinson and Waters’ needs analysis, covering necessities, lacks, and wants. The results demonstrate that students view English as important for continuing their education, developing careers, and promoting fashion products internationally. However, many students still struggle with grammar, pronunciation, and speaking, and have limited opportunities to practice English outside the classroom. Vocabulary, writing, and reading are among the most needed language components, particularly for describing products and engaging with global fashion trends. Students also expressed a strong preference for materials that are directly related to fashion and for interactive learning methods such as group work and class discussions. These findings highlight the need to develop more relevant ESP instruction that reflects the realities and expectations of the fashion design field. Teachers are encouraged to adjust lesson plans to better support students’ language development for both academic and professional purposes.